Factors related to childbearing in Bangladesh: a generalized linear modeling approach - Asaduzzaman, Md.; Khan, Md. Hasinur Rahman (BRAC University, 2010)
Childbearing is generally considered as an important and major determinant of large family size and rapid population growth, particularly in the countries where family planning is not widely practiced. Bearing more children produces substantial risks to the health of the mothers and the children. This paper aims to determine the different factors of childbearing among the ever-married women in Bangladesh. Bangladesh Demographic Health Survey data 1999-2000 and 2004 have been used for this study. A generalized linear model with Poisson link function is used to determine the key socio-economic and demographic factors of childbearing in Bangladesh. Mother's age group, educational level, types of place of residence, age at first marriage, division, having radio etc. are found to be significantly associated with bearing more children in Bangladesh.